2010
DOI: 10.2165/11587990-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide and Non-Invasive Haemodynamics and Hydration Status Assessments in the Management of Patients with Acute Heart Failure in the Emergency Department

Abstract: Introduction: An impairment of cardiac haemodynamics and fluid retention may occur in patients with acute heart failure (AHF) because of left ventricular (LV) dysfunction due to volume and or pressure overload. The measurement of B-type natriuretic peptide (BNP) represents the 'gold standard' of biomarker assessment for evaluating LV adaptations to AHF. More recently, Nexfin and bioelectric impedance vector analysis (BIVA) techniques have been proposed for non-invasively assessing haemodynamic and hydration st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Moreover, HI seems to be a quantitative parameter that can be used independently of gender, differently from a BIVA nomogram. 13,26 We share similar results with Parrinello et al, 27 although our data also suggest that assessing peripheral congestion with BIVA may provide additional clinical utility, especially when BNP provides little help. It is well known that a value of BNP between 100 and 400 pg/ml is considered to be a 'grey zone' and a BNP value included in this range is difficult to interpret as diagnostic of AHF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, HI seems to be a quantitative parameter that can be used independently of gender, differently from a BIVA nomogram. 13,26 We share similar results with Parrinello et al, 27 although our data also suggest that assessing peripheral congestion with BIVA may provide additional clinical utility, especially when BNP provides little help. It is well known that a value of BNP between 100 and 400 pg/ml is considered to be a 'grey zone' and a BNP value included in this range is difficult to interpret as diagnostic of AHF.…”
Section: Discussionsupporting
confidence: 89%
“…9,29 Because clinical and preclinical fluid retention is one of the most frequent causes of re-hospitalizations in AHF patients, a rapid and inexpensive instrument for quantifying peripheral oedema at the moment of a patient's presenting in ED could be an important prognostic tool with which the emergency physicians could immediately assess a risk stratification of these patients. 2,26,30 Previous data from our group 15 demonstrated that sequential BIVA measurements in AHF patients results in an improvement of patients' outcomes linked to optimizing diuretic treatment. In that study we also showed a correlation with events at three months in patients with mean hydration values >80% at the moment of hospital discharge.…”
Section: Nri Of Hi Plus Bnp In Patients Withmentioning
confidence: 99%
“…The BIVA technique was developed at the University of Padua (Italy) (7) . The machine uses an alternating current fl ux of 800 μ A and an operating frequency of 50 kHz.…”
Section: Bio-electrical Impedance Vector Analysis (Biva)mentioning
confidence: 99%
“…In this important scenario, several studies have investigated and have further confi rmed the emerging role of biomarkers, such as natriuretic peptides (NPs) (5) , assisted by bio-impedance vector analysis (BIVA) in the management of congestion due to increased TBW content in the setting of chronic heart failure (CHF) or acute heart failure (AHF) patients (6,7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation